To find the equation that represents Bryan's balance after \( n \) minutes, we first need to determine the rate at which his balance decreases per minute.
Let's analyze the information provided:
- After 1 minute, his balance is $45.
- After 2 minutes, his balance is $38.
- After 3 minutes, his balance is $31.
From this, we can see how much his balance decreases each minute:
- From minute 0 to minute 1: \( 52 - 45 = 7 \) (balance decreased by $7)
- From minute 1 to minute 2: \( 45 - 38 = 7 \) (balance decreased by $7)
- From minute 2 to minute 3: \( 38 - 31 = 7 \) (balance decreased by $7)
This shows that Bryan is charged $7 per minute.
Now, we write the equation to represent the balance after \( n \) minutes.
The total balance can be calculated as:
\[ \text{Balance} = \text{Initial Balance} - (\text{Charge per minute} \times n) \]
Given:
- Initial balance = $52
- Charge per minute = $7
Thus, the equation for the balance \( B \) after \( n \) minutes is:
\[ B = 52 - 7n \]
So the completed equation is:
\[ B = 52 - 7n \]